A Study of Students’ Learning Outcomes Based on National Qualifications Framework for High Education in Thailand from the 5K Model Based Classroom in Rambhai Barni Rajabhat University - Jensen, Tommy; Jaimaitee , Thitikan; Siritanpon, Eaksuwat; Suchairatanachoke, Aungsumarin; Wongchai , Winitchaya (Journal of Roi Et Rajabhat University, 2021)
The objectives of this research were to study all 3 issues as follows: 1) to study the learning achievement by applying the teaching innovation in the form of 5K Model, affected to developing skills according to the National Higher Education Qualifications Framework (TQF), 2) to investigate the students’ retention of learning achievement in relation to the National Higher Education Qualifications Framework (TQF), 3) to study the students’ satisfaction on 5K Model regarding the National Higher Education Qualifications Framework (TQF). The samples were 145 undergraduate students of Rambhai Barni Rajabhat University, Chanthaburi Province, which was selected by simple random method. The research instruments were a record of moral behavior, ethics and responsibility, pre-test and posttest as well as satisfactory questionnaires. The descriptive statistics used as the data analysis tools were percentage, mean, standard deviation and variance. The results revealed that the students taught by 5 K Model in accordance with five aspects of the National Higher Education Qualifications Framework (TQF), had higher learning outcomes in all aspects, obviously, the knowledge aspect. The learning outcome before learning had higher scores than after learning in all 5 aspects. The students’ retention of learning outcome after two weeks of learning was at the 0.05 of significant difference. Also, the students’ satisfaction on 5 K Model learning was at the high level of 4.40.